Sulfur removal from ionic liquid-assisted coal water slurry electrolysis in KNO3 system - Chen, Z.; Gong, X.; Wang, Z.; Wang, Y.; Zhang, Shu; Xu, D. (2013)
Ionic liquid-assisted coal water slurry (CWS) electrolysis was carried out in KNO 3 system with constant current. The effects of ionic liquids including structure, concentration, temperature and time on the removal of sulfur were investigated to intensify desulfurization ratio from CWS electrolysis. Given the organic structure of imidazole, the influence of anions on the desulfurization was in the following order: Br - > BF 4 - > Cl - . Given the same anion of Br - , imidazole showed better performance than pyridine in terms of sulfur elimination. With increasing N-butylpyridinium bromide ([BPy]Br) concentration, the desulfurization ratio increased at the initial stage, and then decreased after 0.30 mol/L. Additionally, the desulfurization ratio continuously increased with time and temperature. Finally, the organic sulfur occurrences in coal before and after experiments were characterized by XPS technique. Results showed that the removal of thiophene was improved due to the extraction-oxidation effects and others (i. e. thioethers and sulfoxide) were removed mainly via enhanced oxidation and hydrolysis reactions.